How biblical languages work : a student's guide to learning Hebrew and Greek - Silzer, Peter J.; Finley, Thomas John. (Grand Rapids, MI : Kregel, 2004)
Introduces first-year Hebrew and Greek grammar students to the characteristics and functions of the language, how the sounds are pronounced and words put together, how words convey meaning, and how languages change.
The big picture: an overview of how language works -- Can you spell that? reading and writing -- Putting it into words: how words are made -- Putting words together: phrases and clauses -- Telling stories and writing letters: understanding discourse -- What do you mean? it's just semantics -- Variety is the spice of life: dialects and change -- Practical ways to study (and learn) the biblical languages.
Includes bibliographical references.
Keywords: Bible. -- Language, style; Hebrew language -- Grammar; Greek language, Biblical -- Grammar